Raja Ram Mohan Roy's Contribution to Women Education - Dr Kshama Sharma (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Raja Ram Mohan Roy (1772–1833) was a visionary reformer whose contributions to women’s education and social reform changed the course of Indian history who Celebrated as the Father of Modern India. In the backdrop of imperial oppression and hardened patriarchy, Roy fought for the eradication of regressive practices like sati and child marriages as well as for the right to widow remarriage and women’s property rights. He was a revolutionary by trying to promote women’s education, stressing the role of modern secular education in increasing women education so that it can empower them and help in the development of society. Roy’s pragmatic agreements with the British administration and his founding of the Brahmo Samaj set up platforms for progressive legislation and social discourse. He has left an important reference for the contemporary policies that aim to remove the gender discrepancies in education and employment, proving that his idea has importance till date in making an egalitarian society. An integration of intellectual advocacy with grassroots mobilization had empowered Raja Ram Mohan Roy, an icon of his time, to become a pioneer and revolutionise Indian society and help in the journey of generations of reformers.